Information systems outsourcing relationship factors: detailed conceptualization and initial evidence - Goles, Tim; Chin, Wynne W. (ACM SIGMIS Database: the DATABASE for Advances in Information Systems, 2005)
Outsourcing is now a commonly accepted means of meeting organizational IS needs. One facet of recent outsourcing research has begun to concentrate on the relationship between customers and their service providers. However, this line of research is hampered by a lack of consistent conceptual focus, and a corresponding inconsistent treatment of constructs associated with the relationship. This paper uses Relational Exchange Theory as a conceptual basis for identifying the individual constructs that comprise a relationship. It then develops and tests a set of items to measure those constructs, using structural equation modeling and survey data collected from U.S. outsourcing customers.